Edible coatings – environmental replacing of traditional candy paper wrapper of «Korivka» candies - Shulga, Oksana; Prutulska, Natalia; Petrusha, Oksana; Smirnova, Elizabeth (My University, 2018)
The article presents a study on the changes occurring in the qualitative and quantitative characteristics of “Korivka” fondant candies when replacing traditional paper wrapper with edible coating. It is expedient to use edible films and coatings for confectionery products in order to comply with the requirements of the Directive 94/62 /EU of the European Parliament and Union on Packaging and Packaging Waste, aimed at minimizing packaging materials waste. Edible coating is made of natural polymers. The proposed composition of edible coating is completely utilized due to its use along with candies.
Keywords: їстівне покриття; упаковка; цукерки; edible coating; packaging; candy; кафедра експертизи харчових продуктів